Conversion of religion in Malaysia: the conflict between the syariah and civil courts systems and its implications / Kamalia Yahdi ...[et al.] - Yahdi, Kamalia; Gorotud, Kristie Cleophas; Hazim, Noorazimah; Ahmad Pauzi, Nur Azhan (2006)
The issues of apostasy are quiet common to be found in the writings of Islamic and Civil law scholars through articles in journals, in printed books, and commonly discussed and presented in seminars. But this is not the situation in the case of conversion. In the above highlight, the research attempts to discuss the implications of conversion within the legal perspectives, in the area of marriage, child custody and inheritance. In doing so, both the Syariah and Civil Courts jurisdiction in the respected area shall be highlighted and noted.